Pedicularis wanghongiae (Orobanchaceae), a new species from Yunnan, southwestern China - Liu, Min-Lu; Yu, Wen-Bin (Phytotaxa, 2015)
Pedicularis wanghongiae M.L.Liu & W.B.Yu, a new species from Gaoligong Mountains in Yunnan Province, southwestern China, is described and illustrated. This new species was found growing in the wet meadow at the top of the mountains near Dulongjiang Township and Cikai Township. Pedicularis wanghongiae is morphologically similar to P. praeruptorum Bonati, but differs from the latter in having an upward bent galea, shorter petioles and only two pubescent filaments. In addition, stems of P. wanghongiae are densely glandular pubescent, and its leaves are abaxially white pubescent along the veins. Furthermore, the pollen grain of P. wanghongiae is bisyncolpate with microfoveolate exine ornamentation. Molecular phylogenetic analyses using four DNA loci (ITS, matK, rbcL and trnL-F) support the delimitation of this new species. Morphologically, this new species should be placed in Pedicularis series Paucifoliatae Prain according to Tsoong’s classification. However, series Paucifoliatae was shown to be paraphyletic based on molecular data. A key to species in series Paucifoliatae is presented, and relationships among these species discussed.